1995
DOI: 10.1111/j.1467-8551.1995.tb00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation and Company Performance: Empirical Evidence From UK Companies

Abstract: There has been little empirical investigation of a relationship between market orientation and performance, which is assumed to exist in the strategic management and marketing literatures. This limited empirical evidence is equivocal, and is dominated by only two US studies. The overall aim of the study reported in this article was to build on this limited empirical evidence about a relationship, by achieving new insights from another national business culture, namely the UK. Unlike the US evidence, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
455
6
18

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(516 citation statements)
references
References 63 publications
(118 reference statements)
37
455
6
18
Order By: Relevance
“…Gatignon&Xuereb (1997) explored which of the three different strategic orientations (customer, competitive, and technological) is suitable for an enterprise. However, a significant number of research papers are related to commercial innovation and innovative performance, whereby some of them refer to the work of the following authors: Zhou et al Greenley (1995), and others. The authors who put the focus of their research on the impact of knowledge and learning orientation upon firm innovativeness are Calantone et al (2002), and Zack (1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gatignon&Xuereb (1997) explored which of the three different strategic orientations (customer, competitive, and technological) is suitable for an enterprise. However, a significant number of research papers are related to commercial innovation and innovative performance, whereby some of them refer to the work of the following authors: Zhou et al Greenley (1995), and others. The authors who put the focus of their research on the impact of knowledge and learning orientation upon firm innovativeness are Calantone et al (2002), and Zack (1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the findings of Atuahene-Gima (1996) fail to confirm his hypothesis that a market orientation influences service innovation performance more strongly than it influences product innovation performance. Greenley (1995) researched a relationship between market orientation and performance in the UK and found that the impact of market orientationon performance was moderated by environmental variables. Moreover, the evidence of Greenley (1995) pointed out that in certain market conditions such as highly turbulent markets, low customer power and high technological change, no advantages might occur as a result of market orientation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the existence of appropriate organisational values as a prerequisite to marketing effectiveness has been identified, 150,151 and is at the root of the marketing orientation literature. This last body suggests clear associations between marketing orientation and performance, [152][153][154][155][156][157] although it has not answered the criticisms implied by the organisational effectiveness literature as discussed earlier.…”
Section: Internal Mediators Of Marketing Strategy Making Processesmentioning
confidence: 99%
“…Part of the value in this picture is that we still have much debate surrounding the benefits of MO. This has helped researchers to identify factors in the MO arena that affect firm performance -firm size, value, goals; influence of external market environment (Greenley, 1995a(Greenley, , 1995b; presence or absence of market competitors, increasing knowledge and management thereof (Delbaere, Sivaramakrishnan, and Bruning, 2003), to name a few. I would kindly welcome anyone to engage in a rigorous reading of these findings.…”
Section: Market Orientation -What Is It?mentioning
confidence: 99%